2001
DOI: 10.1063/1.1383570
|View full text |Cite
|
Sign up to set email alerts
|

Molecular spectroscopy of dye aggregates by scanning-tunneling-microscope-induced light emission

Abstract: A bromide-modified silver (111) surface, covered by Jelly-type aggregates of a cyanine dye, is investigated by scanning tunneling microscopy (STM) in air. We show that, under appropriate conditions, light is emitted out of the junction by inelastic electron tunneling. Study of the relation between the light intensity and the tunnel bias clearly reveals a molecular influence on the light emission. Furthermore, through a spectral analysis, we show that sharp resonances appear for dye-covered surfaces by coupling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The adsorption of molecules on metal surface is known to modify the plasmon-mediated emission spectra as the molecule acts as a spacer to change the dielectric property and junction geometry between the tip and surface [16 -18]. On the other hand, other reports suggest the contribution of molecular fluorescence to the STM-LE spectrum [14,15].…”
Section: Introductionmentioning
confidence: 98%
“…The adsorption of molecules on metal surface is known to modify the plasmon-mediated emission spectra as the molecule acts as a spacer to change the dielectric property and junction geometry between the tip and surface [16 -18]. On the other hand, other reports suggest the contribution of molecular fluorescence to the STM-LE spectrum [14,15].…”
Section: Introductionmentioning
confidence: 98%
“…Extensive research of STM-induced luminescence has been reported on metal surfaces, 2,3 semiconductors, 4,5 and molecules. [6][7][8] Early studies of STM-induced luminescence from C 60 molecules adsorbed on Au͑111͒ suggested that photon emission was from molecules. 6 Only until 2002, Hoffmann et al 9 demonstrated that the adsorbed molecules in the first monolayer ͑ML͒ act merely as spacers to modify plasmon mediated emission from the metal surface.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] They exhibit a narrow and red-shifted electronic absorption band ͑J band͒ and strong fluorescence with a small Stokes shift. These characteristic optical properties, which are the origins of their expected functions, are nicely explained by the interaction between the transition dipole moments ( tr 's͒ of the dyes arranged in the so-called ''head-to-tail'' manner.…”
Section: Introductionmentioning
confidence: 99%